LEXICAL DENSITY DAN GRAMMATICAL INTRICACY MATERI BACAAN PADA BUKU BAHASA INGGRIS KELAS 6 SD - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2011)
The study on lexical density (LD) and grammatical intricacy (GI) is aimed at construing: (1) the LD index of the texts of English textbooks for sixth graders; (2) the GI index of the texts of English textbooks for sixth graders; and (3) whether both indices are tolerable. The data of this study are all the texts of the textbooks presumably being used by Semarang sixth graders. The results are: (1) the LD index is 0.54; (2) the GI index is 1.19; and (3) both LD and GI indices are significantly low. Pedagogically, the results imply that the texts may easily be comprehended by Semarang sixth graders, although, some of the reading texts are written in complex sentences. This, somehow, creates a difficulty on the part of the students. However, in order to justify whether a text is really useful, a further researcher could provide information pertaining to the readability and the generic structure potential of the text. Key words: lexical density, grammatical intricacy, content words, running words.